Elias, ultra-realism and double-binds: Violence in the streets and the state - Clement, Matt (European journal of criminology, 2022)
?Ultra-realism? has become an influential current in criminology, especially in the study of violence and explanations of trends in violent crime. Ultra-realist writers frequently make use of Norbert Elias?s theory of civilizing processes, while also often expressing reservations about his ideas. In this article, we argue that ultra-realists tend to make only partial and inaccurate use of Elias?s very extensive writings. Although he himself did not write very much about crime ? and indeed was less concerned with violence per se than with the roots of aggressive impulses and their control ? we place him in the context of the post-war sociology of deviance. We argue in particular that it is far from true that he was blind to political economy, since the state-formation processes are central to his theory. We relate our argument to double-bind processes, violent subcultures, moral panics, populism and recent political developments in Britain.